Studi Komparasi Metode Eksperimen Inkuiri dengan Eksperimen Verifikasi terhadap Hasil Belajar IPA Materi Perpindahan Kalor - Izza Aliyatul Muna (IAIN Ponorogo, 2017)
This study aims to compare students' learning outcomes in the subject of heat transfer using an inquiry experimental method and a verification experiment. The sampleswere PGMI class students which were selected using the purposive sampling technique. The datawere gained from the learning result of the cognitive domain of students obtained from the pre-test and post-test scores which were analyzed by using t-test of two variant equations and psychomotor domain learning result. The students' cognitive learning outcome using inquiry learning (N-gain 56.98%) differed significantly higher than that using verification experimental method (N-gain 39.58%). Meanwhile, in term ofpsychomotor aspects covering the skills of assembling tools in practicum, using practicum equipment, performing experiments according to procedures, taking data in practice, and presenting observation, the learning outcomes usinginquiry experimental method and verification experiment were respectively 77.06% and 74.91%. Thus, it revealed that there was no a significant difference between the use of inquiry experimental method and the verification experimental method on psychomotor aspect learning outcomes on the subject of heat transfer.حاول هذا البحث مقارنة نتائج تعلّم الطلاب في مادة انتقال الحرارة باستخدام طريقة التجربة التحقّقية والتجربة التحقيقية. وعينة هذا البحث هو الطلاب في قسم التربية لمدرسي المدارس الإبتدائية (أ) بأسلوب أخذ العينات المتعمدة ، أما بيانات هذا البحث فهو نتائج الطلاب للجانب المعرفي والجانب النفسحركي المحصولة عليها من الاختبار القبلي والاختبار البعدي وتُحلّل باستخدام اختبار t في التشابه في اثنين بين المتغيّرات. فنتائج التعلم للجانب المعرفي في مادة انتقال الحرارة باستخدام طريقة التجربة التحقيقية ( N-gain 56,98%) ويختلف أكثر وهو أعلى من التعليم باستخدام الطريقة التجربة التحققية. (N-gain 39,58%). ونتائج التعلم للجانب النفسحركي المشتمل على مهارة تنسيق وتعليق الأدوات المستخدمة في عمل المختبر، واستخدامها، والقيام بالتجربة طبقا للخطوات المقررة، واتخاذ البيانات في عمل المختبر، وعرض نتائج الملاحظة باستخدام طريقة التجربة التحقيقية (77.06% ) لا يختلف كثيرا عن طريقة التجربة التحققية (74,91%) . بهذا لا يوجد فرق كبير بين استخدام طريقة التجربة التحقيقية وطريقة التجربة التحققية تجاه نتائج التعلم في الجانب النفسحركي في مادة انتقال الحرارة.